ANTI-CORRUPTION IDEOLOGY IN HIGHER EDUCATION IN INDONESIA - Sulaiman Sulaiman (Student Journal of International Law, 2021)
Anti-corruption ideology will get through deeply into the system of beliefs. Individuals with anti-corruption ideals are strengthened with their values, ideas, and norms, saying that corruption is atrocious. One of the potential opportunities for instilling the beliefs system is in higher education, where the education and teaching process and its recycling are taking place. The educational process at a higher education level is considered more established in understanding various levels of sciences and knowledge. Therefore, higher education has the greatest potency to ingrain anti-corruption ideals and encourage resistance against corrupt behavior. However, the potential is still debatable because educated persons conduct corruption, as it has been categorized as white-collar crime. Figures displayed by corruption statistics are outrageous. First, the rate of corruption targeted for investigation, being investigated, and punished is growing. Second, there is a tendency that the more a person developed, becomes more respected and educated, the more chances for the person to have a corrupted mindset. Hence, it can be concluded that education does not cause neglectfulness and powerlessness of someone to avoid corruption, but their intellectuality determines it. Keywords: Ideology; Epistemology; Anti-corruption; Higher education.